Some Economic Aspects of the New Long and Short Haul Clause - Clark, J. M. (Quarterly Journal of Economics, 1914)
Early interpretation of this clause, 323. — I. Cases in which relief is granted; the general policy, 325. — Roundabout lines, 327. — Crosslines, 328. — Market competition, 330. — The parallel of a protective tariff, 332. — II. Extent of relief granted, 333. — Recent trans-continental rate cases, 334. — The zone method criticised, 335. — Conclusion: the margin of tolerance and the Commission's ideal, 336.